Don’t pin it all on a stereotype - LU, Chirag; Kalra, Pramila; NA, Arivazhagan; Shashidhar, Abhinith; Singh, Gyani Jail; Saini, Jitender (Indian Journal of Case Reports, 2024)
Hypercalcemia is one of the most frequently encountered problems in endocrinology OPD. Although the evaluation may not always be straightforward in all scenarios. Common factors affecting calcium levels such as dehydration, improper sample collection, and vitamin D supplementation may mask a serious underlying disorder. Here, we discuss a case of an elderly female who had symptoms of myelopathy and hypercalcemia whose etiology was initially attributed to excessive supplementation of calcium, vitamin D, and age- related bone changes; had another serious underlying calcium metabolism disorder.